Implementation of Discharge Planning Cardiac Catheterization on the Readiness of Acute Coronary Syndrome Patients - Sari Ratna Dewi; Blacius Dedi; Asep Badrujamaludin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to see the effectiveness of implementing cardiac catheterization removal in admitting patients with acute coronary syndrome at Immanuel Hospital Bandung. This type of research is quasi-experimental with nonequivalent pre- and post-test control groups only. The research results obtained by implementing cardiac catheterization removal planning in the intervention group effectively admitted patients with acute coronary syndrome at Immanuel Hospital Bandung. There was no significant difference between the control group and the intervention group in the patient's readiness to carry out the discharge plan but within a period of <30 days in the control group, there were data on three patients who were readmitted, while in the intervention group, there were no readmissions. In conclusion, planned-release cardiac catheterization is effective in patients with acute coronary syndrome. Keywords: Discharge Planning, Cardiac Catheterization, Readmission, Acute Coronary Syndrome